Pentingnya keterampilan public speaking dan personal grooming dalam membangun hubungan terhadap nasabah pada ruang lingkup perbankan syariah - Dunakh, Fatimah Tasya Rabhita Selba (Maliki Interdisciplinary Journal, 2024)
This research examines the importance of developing public speaking and personal grooming skills for employees in the context of Islamic banking, with a specific focus on their pivotal role in building effective relationships with customers. Through a qualitative research approach, this study explores how public speaking and personal grooming skills can enhance the professional image of employees and to what extent they can strengthen the bonds and trust of customers towards Islamic banking institutions. Data were collected through in-depth the results of training held by the Faculty of Economics for Islamic Banking students. The findings indicate that effective public speaking skills can enhance the communicative appeal of employees, while personal grooming contributes to the perception of professionalism and self-confidence. The combination of these skills is recognized as a key factor in shaping positive relationships with customers, creating a friendly and trustworthy environment. The implications of this research provide valuable insights for Islamic banking management in designing employee development programs that focus on communication and personal appearance aspects to improve positive interactions with customers.